Human milk cortisol concentration predicts experimentally induced infant fear reactivity: moderation by infant sex - Nolvi Saara; Uusitupa Henna-Maria; Bridgett David J; Pesonen Henri; Aatsinki Anna-Katariina; Kataja Eeva-Leena; Korja Riikka; Karlsson Hasse; Karlsson Linnea (Wiley, 2022)
Little consideration has been given to the possibility of human infant development being shaped via lactocrine programming, and by breast milk cortisol levels specifically. Despite animal models indicating that glucocorticoid (GC) exposure via lactation might modify brain development and behavior, only one study has reported that milk cortisol levels were positively associated with infant negative affectivity, especially fearfulness and sadness—early emerging risk factors for internalizing difficulties such as anxiety. The aim of the current study was to investigate whether human milk cortisol is associated with mother-reported fearfulness and experimentally induced infant fear reactivity. Mother-infant dyads (n = 65) enrolled in the FinnBrain Cohort Study participated. Breast milk samples were obtained 2.5 months postpartum, and milk cortisol concentrations were ascertained using validated luminescence immunoassay methodology. Infant fear reactivity was assessed using maternal reports 6 months postpartum and in a laboratory 8 months postpartum. There was a significant interaction between infant sex and milk cortisol such that higher milk cortisol was related to higher infant fear reactivity in a laboratory setting in girls (β = 0.36, p = .04) but not in boys (β = −0.15, p = .40). Milk cortisol was not associated with mother-reported infant fearfulness. Results suggest that higher human milk cortisol concentrations are associated with elevated experimentally induced fear in infancy. Findings support lactocrine programming, and suggest that mothers may “communicate” vital information about stressful environments via cortisol contained in breast milk, shaping girls’ early emotional reactivity.